1995
DOI: 10.1074/jbc.270.9.4729
|View full text |Cite
|
Sign up to set email alerts
|

The Product of the Herpesvirus saimiri Open Reading Frame 1 (Tip) Interacts with T Cell-specific Kinase p56lck in Transformed Cells

Abstract: Subgroup C strains of Herpesvirus saimiri, a leukemogenic virus of non-human primates, transform human T cells to permanent growth in culture. These cell retain their antigen specificity, and they are becoming widely used as a model for activated human T cells. Though a variety of human cell types can be infected by H. saimiri, transformation appears to be specific for CD4+ and CD8+ T cells. Our investigation of early signaling events in H. saimiri-transformed T cells revealed a novel 40-kDa phosphoprotein com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
132
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 38 publications
7
132
1
Order By: Relevance
“…Both corresponding proteins, tyrosine kinase-interacting protein (Tip) and H. saimiri transformation-associated protein of C strains (STP-C), are absolutely required for growth transformation (19) and interact with signaling proteins. Tip binds to Lck and is phosphorylated by Lck (20). In most (21-23) but not all assay systems (24) Tip activated Lck.…”
Section: Fig 4 Mapk Phosphorylation Primary Cd4mentioning
confidence: 99%
“…Both corresponding proteins, tyrosine kinase-interacting protein (Tip) and H. saimiri transformation-associated protein of C strains (STP-C), are absolutely required for growth transformation (19) and interact with signaling proteins. Tip binds to Lck and is phosphorylated by Lck (20). In most (21-23) but not all assay systems (24) Tip activated Lck.…”
Section: Fig 4 Mapk Phosphorylation Primary Cd4mentioning
confidence: 99%
“…The other protein was termed Tip, for tyrosine kinase interacting protein. Tip was found to tightly bind p56 lck both in vitro and in vivo, without any measurable interaction with other Src family members (5). Subsequent evidence has shown that Tip dramatically increases the tyrosine kinase activity of p56 lck , and this appears to be by inducing a conformational change (6,7).…”
mentioning
confidence: 99%
“…14,16 The transformation-associated genes, tyrosine kinase-interacting protein (tip) and saimiri transformation-associated protein of subgroup C (stpC) are located at the left end of the L-DNA. 17,18 They are translated from a single bicistronic mRNA, and their transcription can be induced by T-cell activation. 19 Although these genes are dispensable for virus replication, their deletion abolishes the transformation capacity of HVS C488.…”
Section: Introductionmentioning
confidence: 99%